The Hygienic, natural and geographical significance in AL-Muntadham book for lbn AI-Jouzy - الاستاذ المساعد الدكتورة فاطمة زبار عنیز الصكري (College of Education for Women, 2019)
This study takes its importance in the area of systemic and historical studies because it stands on presenting such aspects from the systematic respect and now Ibn AL-Jouzy dealt with the text of this subject and how he was exact in telling them. Therefore, this study sheds light on the important aspects of this method in his book through reading and studying such texts whether they had direct or indirect relationship with this subject. This study is not an easy task since it is based on contriving the intellectual aspects in the methods of lbn AL-Jouzy and how he deals with the text of this subject in its hygienic, natural and geographical aspects in constructing a historical method in most scripts, the general and the specific.